2014
DOI: 10.1093/mnras/stu2532
|View full text |Cite
|
Sign up to set email alerts
|

Variation of galactic cold gas reservoirs with stellar mass

Abstract: The stellar and neutral hydrogen (H i) mass functions at z ∼ 0 are fundamental benchmarks for current models of galaxy evolution. A natural extension of these benchmarks is the two-dimensional distribution of galaxies in the plane spanned by stellar and H i mass, which provides a more stringent test of simulations, as it requires the H i to be located in galaxies of the correct stellar mass. Combining H i data from the ALFALFA survey, with optical data from SDSS, we find a distinct envelope in the H i-to-stell… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
152
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(170 citation statements)
references
References 48 publications
15
152
3
Order By: Relevance
“…Catinella et al 2010;Huang et al 2012;Maddox et al 2015), however, our relations do not appear to show evidence of any break.…”
Section: Broken Scaling Relationscontrasting
confidence: 72%
See 1 more Smart Citation
“…Catinella et al 2010;Huang et al 2012;Maddox et al 2015), however, our relations do not appear to show evidence of any break.…”
Section: Broken Scaling Relationscontrasting
confidence: 72%
“…Using the HI-selected population of ALFALFA, Huang et al (2012) found that the scaling relation between stellar mass and HI mass has a slope change at a stellar mass of about 10 9 M , and this result was confirmed in Maddox et al (2015) via a similar analysis of the ALFALFA dataset. The fact that such a break in the scaling relation is not apparent in our dataset does not indicate a conflict with these results because the break is expected to occur at M * ∼ 10 9 M and our dataset begins at L B ∼ 10 9 L (although stellar mass and B-band luminosity are not directly equivalent they should be the same order of magnitude).…”
Section: Broken Scaling Relationsmentioning
confidence: 76%
“…In this work we perform a crude selection on the semi-analytic galaxies, converting the HI mass to a HI flux by setting an observer at the centre of the simulation box. We see from the top panel of Figure 5 that our model galaxies span the same range of stellar mass as the ALFALFA data and show the same upper limit in gas fraction (Maddox et al 2015). However, the median ratio is offset significantly from that observed by AL-FALFA.…”
Section: Gas Fractionssupporting
confidence: 59%
“…Given that disk mass and D/T (= 1 -B/T ) correlates with gas mass and gas fraction (e.g., Saintonge et al 2011;Maddox et al 2015), it is likely that these variables give information on what remains to be quenched in a given galaxy, and hence how much work must be done to quench it. Alternatively, central velocity dispersion (which is known to correlate strongly with dynamically measured MBH ) likely gives information regarding the available energy to do work quenching the system.…”
Section: Results For Centralsmentioning
confidence: 99%